Association Between Anthropometric Measures and Long‐Term Survival in Frail Older Women: Observations from the Women's Health Initiative Study. Issue 2 (February 2016) - Zaslavsky, Oleg; Rillamas‐Sun, Eileen; LaCroix, Andrea Z.; Woods, Nancy F.; Tinker, Lesley F.; Zisberg, Anna; Shadmi, Efrat; Cochrane, Barbara; Edward, Beatrice J.; Kritchevsky, Stephen; Stefanick, Marcia L.; Vitolins, Mara Z.; et al.
Abstract : Objectives: To evaluate the association between currently recommended guidelines and commonly used clinical criteria for body mass index (BMI), waist circumference (WC), and waist‐to‐hip ratio (WHR) and all‐cause mortality in frail older women. Design: Longitudinal prospective cohort study. Setting: Women's Health Initiative (WHI)—Observational Study. Participants: A sample of women aged 65–84 with complete data to characterize frailty in the third year of WHI follow‐up (N = 11, 070). Measurements: Frailty phenotype was determined using the modified Fried criteria. Information on anthropometric measures (BMI, WC, WHR) was collected in clinical examinations. Cox proportional hazards models were used to estimate the effect of BMI, WC, and WHR on mortality adjusted for demographic characteristics and health behaviors. Results: Over a mean follow‐up of 11.5 years, there were 2, 911 (26%) deaths in the sample. Women with a BMI from 25.0 to 29.9 kg/m 2 (hazard rate ratio (HR) = 0.80, 95% confidence interval (CI) = 0.73–0.88) and those with a BMI from 30.0 to 34.9 kg/m 2 (HR = 0.79, 95% CI = 0.71–0.88) had lower mortality than those with a BMI from 18.5 to 24.9 kg/m 2 . Women with a WHR greater than 0.8 had higher mortality (HR = 1.16, 95% CI = 1.07–1.26) than those with a WHR of 0.8 or less. No difference in mortality was observed according to WC. Stratifying according to chronic morbidity or smoking status or excluding women with early death and unintentional weight loss did not substantially change these findings. Conclusion: In frail, older women, having a BMI between 25.0 and 34.9 kg/m 2 or a WHR of 0.8 or less was associated with lower mortality. Currently recommended healthy BMI guidelines should be reevaluated for frail older women.